2018
DOI: 10.1002/jcb.27943
|View full text |Cite
|
Sign up to set email alerts
|

New generation CPPs show distinct selectivity for cancer and noncancer cells

Abstract: In the last three decades, many new cell‐penetrating peptides (CPPs) were developed that exhibited enhanced cell selectivity. Thus, we aimed to validate the tumor cell selectivity of peptides from this new generation, namely fragments mini‐crotamine and mini‐maurocalcine. Both of these peptides are derived from venoms. Furthermore, we studied an analog of the classical CPP HIV‐TAT(47‐57) with alternating chirality of Arg residues. To allow covalent coupling of cargoes or fluorophores, a cysteine residue was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(194 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, the ability of crotamine to transport cargoes both in vitro and in vivo, in particular into actively proliferating cells, 59 makes crotamine and its derivatives suitable markers of actively proliferating cells, such as cancer cells. For instance, very recently Tansi et al 23 found that a fluorescent derivative of Cys‐[4‐Ser‐crotamine(Δ10–37)] could reveal tumor micro‐heterogeneity by preferential internalization into proliferating breast cancer cells, whereas it was homogeneously distributed in fibrosarcoma, colon cancer, and noncancerous endothelial cells. Thus, this peptide can be used to determine the level of heterogeneity within tumors.…”
Section: Cationic Cppsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ability of crotamine to transport cargoes both in vitro and in vivo, in particular into actively proliferating cells, 59 makes crotamine and its derivatives suitable markers of actively proliferating cells, such as cancer cells. For instance, very recently Tansi et al 23 found that a fluorescent derivative of Cys‐[4‐Ser‐crotamine(Δ10–37)] could reveal tumor micro‐heterogeneity by preferential internalization into proliferating breast cancer cells, whereas it was homogeneously distributed in fibrosarcoma, colon cancer, and noncancerous endothelial cells. Thus, this peptide can be used to determine the level of heterogeneity within tumors.…”
Section: Cationic Cppsmentioning
confidence: 99%
“…Indeed, to highlight tumors or inflamed tissues, marker molecules must be conjugated. For instance, fluorescent labels can be used as markers, 21 especially those emitting in the near‐infrared (NIR) region, 22,23 together with metal‐chelating complexes for sensitive NMR imaging 24 and radionuclides 25 . Therefore, imaging with fluorescence‐labeled and tissue‐specific CPPs can be very helpful for visualizing the margin between healthy and diseased tissues during surgery 4 …”
Section: Introductionmentioning
confidence: 99%
“…Overall, in a series of sequential studies, replacing the cysteine residue at position 4 in NrTP-1 for a serine resulted in an analog, namely NrTP-6 (YKQSHKKGGKKGSG), with a significantly improved performance in terms of its interaction with biomembranes, penetrability, cargo transportation of large macromolecules, concentration-independent internalization kinetics and negligible cytotoxicity to healthy cells [148][149][150][151]. The NrTP-6 analog, in which the near-infrared dye DY676 was coupled to an extra N-terminal cysteine residue in NrTP-6 (DY676-Cys-NrTP6, "mini-crotamine") efficiently penetrated and accumulated in certain lines and cancer cell populations, rendering this NrTP version a promising theranostic probe for imaging cancer heterogeneity and delivery of chemotherapeutics into subpopulations of cancer cells [152].…”
Section: Crotaminementioning
confidence: 99%
“…This toxin is specifically uptaken by actively proliferating cells, being able to permeate several lineages in vitro (Nascimento et al, 2007). Additionally, several molecules based on crotamine structure, including fluorescent derivatives (Tansi et al, 2019) and functionalized with gold nanoparticles (Karpel et al, 2018), for instance, are being developed. Crotamine and its analogues have been tested in healthy and tumorous cell lines, and the results indicate they can be used as selective delivery tools of anticancer molecules (Mambelli-Lisboa et al, 2018).…”
Section: Snakesmentioning
confidence: 99%